(untitled) (Revista da Faculdade de Odontologia - UPF, 2025)
Aim: HIV-associated oral lesions may serve as predictive indicators of immunosuppression, assisting in both the diagnosis and monitoring of disease progression in affected patients. Therefore, this study aimed to retrospectively analyse biopsied HIV-associated oral lesions diagnosed by a specialised histopathology service, with emphasis on patient and lesion characteristics. Materials and methods: A retrospective cross-sectional study was conducted to analyse cases of HIV-associated oral lesions from the DCOD, covering records from January 1981 to December 2024. Results: Among the 26,947 reports analysed, 83 were suggestive of HIV-associated lesions, of which 24 patients had confirmed infection. Kaposi sarcoma and non-Hodgkin lymphoma were the most frequent diagnoses. Most patients were male (75%), with a mean age of 46 years (SD = 14.91). Conclusion: This retrospective study met its objectives by characterising the demographic profile of affected patients and describing the clinical features of HIV-associated oral lesions diagnosed at a regional referral centre